2022
DOI: 10.1021/acssuschemeng.1c06845
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Plastics in the United States: Plastic Material Flows and Polyethylene Terephthalate (PET) Recycling Processes

Abstract: As efforts are made toward establishing a circular economy that engages in activities that maintain resources at their highest values for as long as possible, an important aspect is understanding the systems which allow recycling to occur. In this article a common plastic, polyethylene terephthalate, i.e., PET or plastic #1, has been studied because it is recycled at relatively high rates in the U.S. as compared to other plastics. A material flow analysis is described for PET resin showing materials collected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…The PP material collected for sorting originates mainly from the containers and other packaging materials such as lids, caps, trays, baskets, and so on. Many studies have been published previously identifying the main challenges and opportunities to promote recovery and recycling of plastics at their EOL. ,, For more information on interpretation of material flows, please refer to Section 6.2 of the SI-1 document and Figure S14 for complete composition of U.S. plastic waste generation by resin type and EOL product categories.…”
Section: Discussionmentioning
confidence: 99%
“…The PP material collected for sorting originates mainly from the containers and other packaging materials such as lids, caps, trays, baskets, and so on. Many studies have been published previously identifying the main challenges and opportunities to promote recovery and recycling of plastics at their EOL. ,, For more information on interpretation of material flows, please refer to Section 6.2 of the SI-1 document and Figure S14 for complete composition of U.S. plastic waste generation by resin type and EOL product categories.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complicated purification of TPA and the harsh reaction conditions for the hydrolysis process severely limit its industrial application. For example, the reaction temperature and pressure for neutral hydrolysis are in the range of 388–693 K and 10–480 bar, respectively. Most works of neutral hydrolysis occur in the noncatalyst systems, and some studies used metal salts as the catalyst . For example, Liu and co-workers used a homogeneous catalyst of Zn­(OAc) 2 to hydrolyze PET at 533 K, and the TPA yield can reach 20% within 1 h .…”
Section: Catalysis Systems For Depolymerization Of Polyestersmentioning
confidence: 99%
“…31−33 Most works of neutral hydrolysis occur in the noncatalyst systems, and some studies used metal salts as the catalyst. 34 For example, Liu and co-workers used a homogeneous catalyst of Zn(OAc) 2 to hydrolyze PET at 533 K, and the TPA yield can reach 20% within 1 h. 35 Wang et al reported that the high concentration of 70%ZnCl 2 /H 2 O can significantly accelerate the PET hydrolysis rate. The yield and purity of TPA reached up to 98.31% and 97.14% at 453 K for 8 h, respectively.…”
Section: Catalysis Systems For Depolymerization Of Polyestersmentioning
confidence: 99%
“…With the help of experimental design, the numerous methods and catalysts used in PET glycolysis can be compared and evaluated more efficiently. Chen and co-workers applied a 2 3 factorial experimental design to study the two-and three-factor interaction effects of reaction temperature, catalyst:PET ratio, and reaction time on the glycolysis of PET. They used cobalt acetate or manganese acetate as catalysts.…”
Section: Introductionmentioning
confidence: 99%